1991
DOI: 10.1159/000468880
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a Truncated M-Type Subunit and Altered Kinetic Properties of 6-Phosphofructo-l-Kinase Isozymes in the Brain of a Dog Affected by Glycogen Storage Disease Type VII1

Abstract: 6-Phosphofructo-1-kinase (PFK) activity in the brain of a dog affected by glycogen storage disease type VII was only 31 % of the PFK activity in the normal dog brain. PFK in the normal dog brain was composed of L-type, M-type and C-type subunits with apparent molecular weights of 78,000, 86,000, and 88,000, respectively, and subunit proportions (L:M:C) of 27:49:24. PFK in the affected dog brain was composed of nearly equal levels of the normal L-type and C-type subunits, but a normal M-type subunit was not det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In contrast to muscle, partially purified extracts of PFK from the erythrocytes and brains of affected dogs showed very small amounts of a lower molecular weight band that was hypothesized to be the truncated M-PFK subunit (14), which has an apparent molecular mass of 84 kDa (32,33). This is 3.3 kDa larger than the predicted molecular weight from the DNA sequence; however, the mobility of proteins in polyacrylamide gels may be affected by factors other than molecular weight, such as glycosylation (34).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast to muscle, partially purified extracts of PFK from the erythrocytes and brains of affected dogs showed very small amounts of a lower molecular weight band that was hypothesized to be the truncated M-PFK subunit (14), which has an apparent molecular mass of 84 kDa (32,33). This is 3.3 kDa larger than the predicted molecular weight from the DNA sequence; however, the mobility of proteins in polyacrylamide gels may be affected by factors other than molecular weight, such as glycosylation (34).…”
Section: Discussionmentioning
confidence: 95%
“…The low residual PFK activity found in muscle (1-4%) could be caused by the mutant M-PFK. Alternatively, there is expression of other PFK isoforms in skeletal muscle (9,14), because in vitro experiments with C2-C12 myogenic cell lines have shown that L-PFK and P-PFK are expressed in myoblasts and at low levels even after myotube formation, indicating that a low expression of these other isoforms in muscle may account for the residual PFK activity (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PFK subunit isoforms were separated using SDS-PAGE and blotted essentially as previously described (54). The primary polyclonal antibodies were rabbit antidog muscle PFK, which recognizes only the M isoform and rabbit anti-rat brain PFK raised against all three isoforms (27).…”
Section: Methodsmentioning
confidence: 99%
“…A point mutation is reported to occur in the muscle-type gene of deficient dogs, causing a loss of amino acids from the carboxyl MS received 17.1.92 Accepted 15.5.92 terminus of the polypeptide . Studies of brain and erythrocytes from affected (homozygous deficient) dogs indicated that native muscle-type subunits were not present, but small amounts of a structurally unstable truncated muscle-type subunit were found (Mhaskar et al 1991(Mhaskar et al , 1992. As would be expected from the subunit composition of normal tissues, total PFK activity in erythrocytes is about 50% of normal in humans (Vora 1982) and 15-20% of normal in dogs (Giger and Harvey 1987).…”
mentioning
confidence: 98%